Soil chemical analysis of gangetic delta plain by combined use of multispectral imagery and XRF spectroscopy - Singh, Neha; Asthana, Harshita; Vishwakarma, Chandrasekhar Azad; Sen, Ratan; Mukherjee, Saumitra (International Journal of Advanced Geosciences, 2016)
24 Parganas districts of West Bengal are very well known for their agricultural productivity. These districts are the part of the mature delta plain of the Bengal delta which is formed by the deposition of weathered sediments through Himalayan Rivers. The agricultural productivity of an area depends mainly upon the fertility of soil which in turn depends on the presence of essential nutrients in it. Thus, the present study was carried out to assess the types of minerals present in the soil which provide the elements that act as the nutrients to the plant. Band ratio technique using the Landsat imagery and X-Ray Diffraction was carried out for the study of mineral composition. XRF was done for the elemental composition of the soil samples and Principal Component Analysis was carried out to assess the sources of these nutrients in the soil. Normalized Difference Vegetation Index was also calculated using Landsat imagery to study the vegetation pattern in the area. The study suggests that the area is mainly comprised of clay and ferrous minerals and contains nearly all the elements that act as macro-and micro-nutrients. However, the study also shows the accumulation of some of the heavy metals which may be due to the excessive use of fertilizers.